2012
DOI: 10.1161/circulationaha.111.075606
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Coronary Blood Flow Velocity With Acute Biventricular Pacing Is Predominantly Due to an Increase in a Diastolic Backward-Travelling Decompression (Suction) Wave

Abstract: Background-Normal coronary blood flow is principally determined by a backward-traveling decompression (suction) wave in diastole. Dyssynchronous chronic heart failure may attenuate suction, because regional relaxation and contraction overlap in timing. We hypothesized that biventricular pacing, by restoring left ventricular (LV) synchronization and improving LV relaxation, might increase this suction wave, improving coronary flow. Method and Results-Ten patients with chronic heart failure (9 males; age 65Ϯ12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 53 publications
1
50
0
1
Order By: Relevance
“…The study would be focused on the integral areas, the main metric used in literature [2], [3], [5]. However, the main waves' peaks accuracy provided by the adaptive S-G algorithms is discussed in the Section IV.…”
Section: Analysis Of Adaptive S-g Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The study would be focused on the integral areas, the main metric used in literature [2], [3], [5]. However, the main waves' peaks accuracy provided by the adaptive S-G algorithms is discussed in the Section IV.…”
Section: Analysis Of Adaptive S-g Accuracymentioning
confidence: 99%
“…Each of the 6 main waves identifiable from the cWIA output [2] are related to a specific event through the cardiac cycle (left ventricle relaxation, aortic valve closure) allowing the coronary measurements to be directly related to their physiological origin. Initially used to investigate the unique feature of the coronary blood flow of being mainly diastolic [2], [3], cWIA recently received increasing attention as a powerful technique to establish a mechanistic link between coronary haemodynamic measurements and the underlying pathopysiology [3]. More recently, De Silva et al [4] demonstrated the prognostic value of a cWIA-derived index in predicting functional recovery following myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%
“…2011; Kyriacou et al. 2012). Recently, a landmark predictive application of WIA was demonstrated for the first time in de Silva et al.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study Kyriacou et al 10 . used cWIA to identify the optimal atrioventricular delay in biventricular pacing in order to improve ventricular contractility and relaxation thereby increasing the cardiac output.…”
Section: Introductionmentioning
confidence: 99%